The palaeoenvironment of the middle Miocene pliopithecid locality in Damiao, Inner Mongolia, China. Issue 108 (July 2017) - Sukselainen, Leena; Kaakinen, Anu; Eronen, Jussi T.; Passey, Benjamin H.; Harrison, Terry; Zhang, Zhaoqun; Fortelius, Mikael
Abstract: Damiao, Inner Mongolia, has three main fossil horizons representing the early, middle, and late Miocene. The middle Miocene locality DM01 is the only primate locality from the region and also represents the latest occurrence of pliopithecoids in northern China. The presence of pliopithecoid primates in central Asia after the middle Miocene climatic optimum seems to contradict the general trend of strengthening climatic zonality and increasing aridity. To investigate this enigma, we employ faunal similarity, ecometrics, and stable isotope analysis. Our results support previous inferences concerning the presence of locally humid environments within the increasingly arid surroundings that characterized central Asia. Hypsodonty, estimated mean annual precipitation (MAP), local sedimentology, and large mammal fossils suggest more humid and possibly more forested and wooded environments for the DM01 locality. We compared our results with the adjacent fossil-rich middle Miocene Tunggur localities. However, the small mammal fauna and isotope data are consistent with a mosaic of forest and grassland environment for all Damiao localities. Based on our results, Tunggur may have been too seasonal or not sufficiently humid for pliopithecids. This is supported by the higher mean hypsodonty and lower estimated MAP estimates, as well as slightly higher δ 13 C values. We suggest that DM01, the driest known Asian pliopithecid locality, may have been a more humid refugium within a generally drier regional context.